Interleukin-18, interleukin-12B and interferon-γ gene polymorphisms in Brazilian patients with rheumatoid arthritis: a pilot study. - Angelo, H D; Gomes Silva, I I F; Oliveira, R D R; Louzada-Júnior, P; Donadi, E A; Crovella, S; Maia, M M D; de Souza, P R E; Sandrin-Garcia, P (Tissue Antigens, 2015)
Polymorphisms in interleukin (IL)-18, IL-12 and interferon (IFN)-γ genes are associated with different levels of cytokines expression and have been associated with rheumatoid arthritis (RA). IL-18 +105 A/C, IL-12B +1188 A/C and IFN-γ +874 T/A polymorphisms were analyzed by restriction fragment length polymorphism-polymerase chain reaction (PCR) and amplification refractory mutation system PCR from 90 RA patients and 186 healthy individuals. There were significant differences to IL-18 +105 A/C polymorphism between the RA and control groups (odds ratio = 3.77; P < 0.0001). Individual carriers of the variant allele C had a 3.77-fold increased risk of for RA (P = 0.0032). No association was observed for IL-12B and IFN-γ polymorphisms. Our finds suggest a possible role for IL-18 polymorphism in the RA susceptibility in studied population.